2014
DOI: 10.1242/jeb.098640
|View full text |Cite
|
Sign up to set email alerts
|

Rh vs pH: the role of Rhesus glycoproteins in renal ammonia excretion during metabolic acidosis in a freshwater teleost fish

Abstract: Increased renal ammonia excretion in response to metabolic acidosis is thought to be a conserved response in vertebrates. We tested the hypothesis that Rhesus (Rh) glycoproteins in the kidney of the freshwater common carp, Cyprinus carpio, play a crucial role in regulating renal ammonia excretion during chronic metabolic acidosis. Exposure to water pH 4.0 (72 h) resulted in a classic metabolic acidosis with reduced plasma arterial pH and , no change in P CO2 and large changes in renal function. Urine [NH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 76 publications
2
52
2
Order By: Relevance
“…In contrast to previous studies in which interpretation was confounded by a decrease in UFR (Wright et al, 2014) and/or an absence of ammonia filtration and secretion measurements (McDonald and Wood, 1981;Wood et al, 1999;King and Goldstein, 1983), the present study clearly revealed the pathways of increased urinary ammonia excretion. In confirmation of our first hypothesis, the elevation in urinary NH 4 + excretion was predominately mediated through increased renal tubular secretion (∼75%), though increased glomerular filtration of ammonia also made a significant contribution (∼25%).…”
Section: Discussion Overviewcontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous studies in which interpretation was confounded by a decrease in UFR (Wright et al, 2014) and/or an absence of ammonia filtration and secretion measurements (McDonald and Wood, 1981;Wood et al, 1999;King and Goldstein, 1983), the present study clearly revealed the pathways of increased urinary ammonia excretion. In confirmation of our first hypothesis, the elevation in urinary NH 4 + excretion was predominately mediated through increased renal tubular secretion (∼75%), though increased glomerular filtration of ammonia also made a significant contribution (∼25%).…”
Section: Discussion Overviewcontrasting
confidence: 99%
“…In contrast to the common carp, which shut down UFR during acid exposure (Wright et al, 2014), goldfish tended to increase UFR, though by 36-48 h, the overall increase was not significant relative to simultaneous controls ( Fig. 1).…”
Section: Secretion Of Ammoniamentioning
confidence: 83%
See 3 more Smart Citations